Positive electrode composite material for all-solid-state sodium ion secondary battery, positive electrode for all-solid-state sodium ion secondary battery, and all-solid-state sodium ion secondary battery

By using a positive electrode composite material containing β"-alumina, β-alumina and NASICON crystals in all solid sodium ion secondary batteries, the shortcomings in existing secondary batteries in high energy density and capacity are solved, and more efficient battery performance is achieved.

CN119790505APending Publication Date: 2025-04-08NIPPON ELECTRIC GLASS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380062035.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-22
Filing Date
2023-11-17
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing secondary batteries are difficult to meet the needs of higher energy density and higher capacity in electric and hybrid vehicles, especially when driving for long distances.

Method used

A positive electrode composite material of an all-solid sodium ion secondary battery is used. This material contains a positive electrode active material and a solid electrolyte. The solid electrolyte contains β"-alumina, β-alumina and sodium superion conductor (NASICON) crystals, and the crystals with the main peak appear at 33° to 34° when measured by powder X-ray diffraction.

Benefits of technology

The capacity of the secondary battery is effectively improved, the thermal expansion coefficient of the positive electrode composite material is optimized, and the circulation characteristics and ion conductivity of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005285587950000151
    Figure BDA0005285587950000151
  • Figure HDA0005285587970000011
    Figure HDA0005285587970000011
  • Figure HDA0005285587970000012
    Figure HDA0005285587970000012
Patent Text Reader

Abstract

Provided is a positive electrode composite material for an all-solid-state sodium ion secondary battery, said positive electrode composite material being capable of effectively improving the capacity of a secondary battery. The positive electrode composite material for an all-solid-state sodium ion secondary battery contains a positive electrode active material and a solid electrolyte containing at least one substance selected from the group consisting of beta ''-alumina, beta-alumina, and a sodium superaionic conductor crystal, and contains a crystal that exhibits a main peak at 33-34 DEG when powder X-ray diffraction measurement is performed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode composite material for an all-solid-state sodium ion secondary battery, and a positive electrode for an all-solid-state sodium ion secondary battery and an all-solid-state sodium ion secondary battery using the positive electrode composite material for an all-solid-state sodium ion secondary battery. Background Art

[0002] Lithium-ion secondary batteries have established their position as an indispensable high-capacity and lightweight power source in mobile devices, electric vehicles, etc. However, in existing lithium-ion secondary batteries, flammable organic electrolytes are mainly used as electrolytes, so there are concerns about dangers such as fire. As a solution to this problem, the development of all-solid-state lithium-ion batteries using solid electrolytes instead of organic electrolytes is underway. However, since lithium has to worry about the rise in raw materials worldwide, the development of all-solid-state sodium-ion batteries is also being promoted.

[0003] The following patent document 1 discloses an all-solid-state sodium ion secondary battery, which includes a positive electrode layer, the positive electrode layer comprising a general formula Na x M y P2O z (M is at least one transition metal element selected from Fe, Cr, Mn, Co and Ni, 1.20≤x≤2.10, 0.95≤y≤1.60) a positive electrode active material crystal represented by.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-097034 Summary of the invention

[0007] Technical problem to be solved by the invention

[0008] In recent years, secondary batteries used as power sources for electric vehicles and hybrid vehicles have been required to have higher energy density and higher capacity for the purpose of long-distance driving.

[0009] An object of the present invention is to provide a positive electrode composite material for an all-solid-state sodium ion secondary battery, a positive electrode for an all-solid-state sodium ion secondary battery, and an all-solid-state sodium ion secondary battery, which can effectively increase the capacity of the secondary battery.

[0010] Technical means to solve problems

[0011] Each aspect of a positive electrode composite material for an all-solid-state sodium ion secondary battery, a positive electrode for an all-solid-state sodium ion secondary battery, and an all-solid-state sodium ion secondary battery that solves the above-mentioned technical problems is described.

[0012] The positive electrode composite material for an all-solid-state sodium ion secondary battery of mode 1 of the present invention is characterized in that it comprises a positive electrode active material and a solid electrolyte, wherein the solid electrolyte contains at least one selected from β"-alumina, β-alumina and sodium superion conductor (NASICON) crystals, and contains crystals showing a main peak at 33° to 34° when performing powder X-ray diffraction measurement.

[0013] In the positive electrode composite material for an all-solid-state sodium ion secondary battery of method 2, in method 1, preferably, when performing the powder X-ray diffraction measurement, the crystal showing a main peak at 33° to 34° is at least one of Na3Fe2(PO4)P2O7 crystals and Na4Fe3(PO4)2P2O7 crystals.

[0014] In the positive electrode composite material for an all-solid-state sodium ion secondary battery of Embodiment 3, in Embodiment 1 or Embodiment 2, it is preferred that the solid electrolyte is at least one of β″-alumina and β-alumina.

[0015] In the positive electrode composite material for an all-solid-state sodium ion secondary battery of method 4, in any one of methods 1 to 3, it preferably contains, by mass%, 30% to 95% of the above-mentioned positive electrode active material, 5% to 70% of the above-mentioned solid electrolyte and 0% to 20% of the conductive aid.

[0016] The positive electrode for an all-solid-state sodium ion secondary battery according to the fifth aspect of the present invention is characterized by including the positive electrode composite material for an all-solid-state sodium ion secondary battery according to any one of the first to fourth aspects.

[0017] The all-solid-state sodium ion secondary battery according to the sixth aspect of the present invention is characterized by comprising the positive electrode for an all-solid-state sodium ion secondary battery according to the fifth aspect.

[0018] Effects of the Invention

[0019] According to the present invention, it is possible to provide a positive electrode composite material for an all-solid-state sodium ion secondary battery, a positive electrode for an all-solid-state sodium ion secondary battery, and an all-solid-state sodium ion secondary battery that can effectively increase the capacity of a secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic cross-sectional view showing an all-solid-state sodium ion secondary battery according to one embodiment of the present invention.

[0021] Figure 2 This is a diagram showing the X-ray diffraction spectra of the positive electrode composite materials for all-solid-state sodium ion secondary batteries prepared in Examples 1 to 3 and Comparative Examples 1 and 2.

[0022] Figure 3 It is a magnified representation Figure 2A graph showing the region of 2θ=30° to 40° in the X-ray diffraction spectrum of . DETAILED DESCRIPTION

[0023] Hereinafter, preferred embodiments will be described. However, the following embodiments are merely illustrative, and the present invention is not limited to the following embodiments. In addition, in each of the drawings, components having substantially the same function are sometimes referred to with the same reference numerals.

[0024] [Positive electrode composite materials for all-solid-state sodium-ion secondary batteries]

[0025] The positive electrode composite material for an all-solid-state sodium ion secondary battery of the present invention comprises a positive electrode active material and a solid electrolyte. The solid electrolyte contains at least one selected from β"-alumina, β-alumina and sodium superion conductor (NASICON) crystals. In addition, the positive electrode composite material for an all-solid-state sodium ion secondary battery of the present invention contains crystals showing a main peak at 33° to 34° when performing powder X-ray diffraction measurement.

[0026] In this specification, the powder X-ray diffraction measurement can be measured by wide-angle X-ray diffraction. As an X-ray source, CuKα rays (wavelength As the X-ray diffraction apparatus, for example, a product number “SmartLab” manufactured by Rigaku Corporation can be used.

[0027] In addition, examples of crystals showing a main peak at 33° to 34° in powder X-ray diffraction measurement include positive electrode active material crystals such as Na3Fe2(PO4)P2O7 crystals and Na4Fe3(PO4)2P2O7 crystals.

[0028] The positive electrode composite material for an all-solid-state sodium ion secondary battery of the present invention contains crystals showing a main peak at 33° to 34° when performing X-ray diffraction measurement, so the capacity of the all-solid-state sodium ion secondary battery can be effectively improved.

[0029] The thermal expansion coefficient of the positive electrode composite material for the all-solid-state sodium ion secondary battery of the present invention is preferably 140×10 -7 / °C or less, more preferably 135×10 -7 / °C or less, more preferably 130×10 -7 / °C or less, particularly preferably 125×10 -7 / °C or less. In this case, the cycle characteristics of the all-solid-state sodium ion secondary battery can be further improved. The lower limit of the thermal expansion coefficient of the positive electrode composite material for the all-solid-state sodium ion secondary battery of the present invention is not particularly limited, and can be, for example, 50×10 -7 / ℃.

[0030] Hereinafter, specific examples of the materials constituting the positive electrode for the all-solid-state secondary battery of the present invention are described. Among them, below, sometimes "positive electrode composite material for all-solid-state sodium ion secondary battery" is referred to as "positive electrode composite material for secondary battery". Sometimes "positive electrode for all-solid-state sodium ion secondary battery" is referred to as "positive electrode for secondary battery". In addition, sometimes "all-solid-state sodium ion secondary battery" is referred to as "secondary battery".

[0031] (Positive electrode active material)

[0032] The positive electrode composite material for secondary batteries of the present invention comprises a positive electrode active material. The positive electrode active material is preferably a crystallized glass containing either Na3Fe2(PO4)P2O7 crystals or Na4Fe3(PO4)2P2O7 crystals. However, the positive electrode active material may also be a crystallized glass containing both Na3Fe2(PO4)P2O7 crystals and Na4Fe3(PO4)2P2O7 crystals.

[0033] In addition, the crystallized glass constituting the positive electrode active material may also contain a general formula of Na 2-x Fe 1+x / 2 P2O7 (0≤x≤1) represented by a crystal. Examples of such a crystal include Na2FeP2O7, Na 3.32 Fe 2.34 (P2O7)2, etc.

[0034] In addition, in this specification, crystallized glass refers to a glass obtained by heating (firing) a precursor glass containing an amorphous phase and precipitating crystals (crystallization). The amorphous phase can be completely transformed into a crystalline phase, or a residual amorphous phase can be left. In addition, one crystal can be precipitated, or more than two crystals can be precipitated. For example, crystallized glass can be distinguished (judged) whether it is crystallized glass based on the peak angle and peak intensity represented by the X-ray diffraction spectrum.

[0035] The crystallinity (crystallinity) of the crystallized glass constituting the positive electrode active material is preferably 70% or more, more preferably 80% or more, further preferably 90% or more, preferably 99% or less. In this case, it is easy to obtain a smooth path for ion diffusion in the positive electrode active material, which contributes to further improvement of battery characteristics.

[0036] The crystallinity of the crystallized glass is obtained from the diffraction line profile with a 2θ value of 10° to 60° obtained by powder X-ray diffraction (XRD) measurement using CuKα rays. Specifically, the integrated intensity obtained by peak separation of a wide diffraction line (amorphous halo) of 10° to 45° in the total scattering curve obtained by subtracting the background from the diffraction line spectrum obtained by powder X-ray diffraction (XRD) measurement is set as Ia, and the sum of the integrated intensities obtained by peak separation of each crystalline diffraction line detected at 10° to 60° is set as Ic, and the crystallinity Xc is obtained by the following formula.

[0037] Xc=[Ic / (Ic+Ia)]×100(%)

[0038] The crystal amount of at least one of the Na3Fe2(PO4)P2O7 crystals and the Na4Fe3(PO4)2P2O7 crystals is preferably 90% by mass or more, more preferably 92% by mass or more, further preferably 95% by mass or more, preferably 100% by mass or less, and more preferably 99% by mass or less. In this case, since there are Na3Fe2(PO4)P2O7 crystals and Na4Fe3(PO4)2P2O7 crystals in which sodium ions are easily diffused compared to Na2FeP2O7 crystals, the discharge capacity can be obtained more reliably even under the condition of high-speed discharge that is prone to polarization.

[0039] In the present invention, the content of the positive electrode active material in the positive electrode composite material for secondary batteries is not particularly limited, and is preferably 30% or more, more preferably 44.5% or more, further preferably 50% or more, preferably 95% or less, more preferably 92% or less, and further preferably 90% or less, in terms of mass%. When the content of the positive electrode active material in the positive electrode composite material for secondary batteries is within the above range, the capacity of the secondary battery can be further effectively increased.

[0040] (Solid electrolyte)

[0041] The secondary battery positive electrode composite material of the present invention includes a solid electrolyte. The solid electrolyte is a component responsible for ion conduction in the secondary battery positive electrode. By including the solid electrolyte, the ion conductivity of the secondary battery positive electrode can be improved even without an electrolyte solution.

[0042] As a solid electrolyte, for example, β-alumina or sodium superion conductor crystals with excellent sodium ion conductivity can be cited. β-alumina exists in two crystal forms: β-alumina (theoretical composition formula: Na2O·11Al2O3) and β"-alumina (theoretical composition formula: Na2O·5.3Al2O3). β"-alumina is usually a metastable substance with Li2O and MgO added as stabilizers. β"-alumina has higher sodium ion conductivity than β-alumina, so it is preferred to use β"-alumina alone, or a mixture of β"-alumina and β-alumina, and it is more preferred to use Li2O stabilized β"-alumina (Na 1.7 Li 0.3 Al 10.7 O 17 ) or MgO stabilized β"-alumina ((Al 10.32 Mg 0.68 O 16 )(Na 1.68 O)).

[0043] As sodium superion conductor crystals, Na3Zr2Si2PO4 can be cited. 12 、Na 3.2 Zr 1.3 Si 2.2 P 0.8 O 10.5 、Na3Zr 1.6 Ti 0.4 Si2PO 12 、Na3Hf2Si2PO 12 、Na 3.4 Zr 0.9 Hf 1.4 Al 0.6 Si 1.2 P 1.8 O 12 、Na3Zr 1.7 Nb 0.24 Si2PO 12 、Na 3.6 Ti 0.2 Y 0.8 Si 2.8 O9、Na3Zr 1.88 Y 0.12 Si2PO 12 、Na 3.12 Zr 1.88 Y 0.12 Si2PO 12 、Na 3.05 Zr2Si 2.06 P 0.95 O 12 、Na 3.4 Zr2Si 2.4 P0.6 O 12 、Na 3.6 Zr 0.13 Yb 1.67 Si 0.11 P 2.9 O 12 and Na5YSi4O 12 As a sodium superionic conductor crystal, Na 3.12 Zr 1.88 Y 0.12 Si2PO 12 Or Na 3.05 Zr2Si 2.06 P 0.95 O 12 It is preferred because of its excellent sodium ion conductivity.

[0044] In the present invention, the content of the solid electrolyte in the secondary battery positive electrode composite material is preferably 5% or more, more preferably 7% or more, further preferably 10% or more, preferably 70% or less, more preferably 55% or less, and further preferably 50% or less. When the content of the solid electrolyte in the secondary battery positive electrode composite material is within the above range, the ion conductivity in the secondary battery positive electrode can be further improved, and the battery characteristics of the secondary battery can be further effectively improved.

[0045] (Conductive additive)

[0046] The secondary battery positive electrode composite material of the present invention may further include a conductive aid. As a conductive aid, for example, conductive carbon can be used. As conductive carbon, for example, acetylene black, carbon black, Ketjen black, vapor-phase carbon fiber conductive aid (VGCF), carbon nanotubes, etc. can be cited. The conductive aid is preferably such a carbon-based conductive aid.

[0047] In the present invention, the content of the conductive auxiliary agent in the secondary battery positive electrode composite material is preferably 0% or more, more preferably 0.5% or more, further preferably 1% or more, preferably 20% or less, more preferably 15% or less, and further preferably 10% or less in terms of mass%. When the content of the conductive auxiliary agent in the secondary battery positive electrode composite material is within the above range, the high electronic conductivity of the secondary battery positive electrode can be ensured, and the ion conductivity can be further improved, which can further effectively improve the battery characteristics of the secondary battery.

[0048] (Method for producing positive electrode composite material for secondary battery)

[0049] The secondary battery positive electrode composite material of the present invention can be formed, for example, by forming an electrode material layer (the electrode material layer further comprises a conductive aid as required) comprising a positive electrode active material precursor and a solid electrolyte powder on the main surface of one side of the solid electrolyte layer described later, and firing the electrode material layer. The electrode material layer can be obtained, for example, by applying a paste comprising a positive electrode active material precursor and a solid electrolyte powder and a conductive aid as required and drying it. Among them, the paste may contain a binder, a plasticizer or a solvent as required. In addition, the electrode material layer may also be a powder press.

[0050] The drying temperature of the paste is not particularly limited, and can be, for example, 40° C. to 120° C. The drying time of the paste is not particularly limited, and can be, for example, 3 minutes to 600 minutes.

[0051] The atmosphere during firing is preferably an inert atmosphere or a reducing atmosphere. The firing temperature (maximum temperature) can be, for example, 400° C. to 600° C., and the holding time at the temperature can be, for example, 1 minute to 2 hours.

[0052] From the viewpoint of making any one of the Na3Fe2(PO4)P2O7 crystals and the Na4Fe3(PO4)2P2O7 crystals precipitate more reliably, the sintering temperature (maximum temperature) is preferably 420°C or more, more preferably 450°C or more, preferably 575°C or less, and more preferably 530°C or less. In addition, the holding time at the temperature is preferably 5 minutes or more, more preferably 10 minutes or more, preferably 1 hour or less, and more preferably 45 minutes or less.

[0053] In addition, the atmosphere during firing is preferably a reducing atmosphere.

[0054] Positive electrode active material precursor:

[0055] The positive electrode active material precursor (positive electrode active material precursor powder) is preferably composed of an amorphous oxide (i.e., amorphous oxide) material that generates active material crystals by firing. When the positive electrode active material precursor powder is composed of an amorphous oxide material, active material crystals can be generated during firing, and softened and flowed to form a dense positive electrode layer. In addition, the integration of the positive electrode active material and the solid electrolyte can also be achieved. Alternatively, when the positive electrode layer is in contact with the solid electrolyte layer, the integration of the two can be achieved. As a result, the ion conduction path is formed better, so it is preferred. In addition, in the present invention, "amorphous oxide material" is not limited to completely amorphous oxide materials, but also includes materials containing a portion of crystals (for example, a crystallinity of less than 10%).

[0056] The positive electrode active material precursor powder preferably contains 25% to 55% of Na2O, 10% to 30% of Fe2O3 and 25% to 55% of P2O5 in terms of mole % of the following oxide conversion. The reason for limiting the composition is described below. In the following description of the content of each component, "%" means "mole %" unless otherwise specified.

[0057] Na2O is the main component of the active material crystal of either Na3Fe2(PO4)P2O7 crystal or Na4Fe3(PO4)2P2O7 crystal. The content of Na2O is preferably 25% to 55%, more preferably 30% to 50%, and further preferably 35% to 45%. When the content of Na2O is within the above range, the capacity of the secondary battery can be further increased.

[0058] Fe2O3 is also the main component of the active material crystal of either Na3Fe2(PO4)P2O7 crystal or Na4Fe3(PO4)2P2O7 crystal. The content of Fe2O3 is preferably 10% to 30%, more preferably 12% to 28%, and further preferably 15% to 25%. When the content of Fe2O3 is above the above lower limit, the capacity of the secondary battery can be further increased. On the other hand, when the content of Fe2O3 is below the above upper limit, it is possible to make it difficult for undesirable crystals such as Fe2O to precipitate.

[0059] P2O5 is also the main component of the active material crystal of either Na3Fe2(PO4)P2O7 crystal or Na4Fe3(PO4)2P2O7 crystal. The content of P2O5 is preferably 25% to 55%, more preferably 30% to 50%, and further preferably 35% to 45%. When the content of P2O5 is within the above range, the capacity of the secondary battery can be further increased.

[0060] The positive electrode active material precursor powder may contain Cr2O3, MnO, CoO, NiO, V2O5, Nb2O5, MgO, Al2O3, TiO2, ZrO2 or Sc2O3 in addition to the above components. The total content of the above components is preferably 0% to 25%, more preferably 0.2% to 10%.

[0061] In addition, the positive electrode active material precursor powder may contain SiO2, B2O3, GeO2, Ga2O3, Sb2O3 or Bi2O3 in addition to the above-mentioned components. By containing these components, the glass forming ability is further improved, and it is easy to obtain a more homogeneous positive electrode active material precursor powder. The content of the above-mentioned components is preferably 0% to 25% in total, and more preferably 0.2% to 10%. Because these components do not contribute to battery characteristics, if their content is too much, there is a tendency for the capacity of the secondary battery to decrease.

[0062] The positive electrode active material precursor powder is preferably prepared by melting (melting) the batched ingredients of the raw materials and forming them. According to this preparation method, it is easy to obtain an amorphous positive electrode active material precursor powder with excellent homogeneity, so it is preferred. Specifically, the positive electrode active material precursor powder can be prepared as follows.

[0063] First, the raw materials are modulated in a manner to obtain a batch batch of raw materials in a desired composition. Next, the obtained batch batch of raw materials is melted. The melting temperature is appropriately adjusted so that the batch batch of raw materials is uniformly melted. For example, the melting temperature is preferably 800° C. or more, more preferably 900° C. or more. The upper limit of the melting temperature is not particularly limited, but if the melting temperature is too high, it will lead to energy loss, evaporation of sodium components, etc., so it is preferably 1500° C. or less, more preferably 1400° C. or less.

[0064] The obtained melt is then formed into a film by a method which is not particularly limited, and for example, the melt may be flowed between a pair of cooling rolls and formed into a film while being rapidly cooled, or the melt may be flowed into a casting mold and formed into an ingot.

[0065] Next, the obtained molded body is crushed to obtain a positive electrode active material precursor powder. The average particle size of the positive electrode active material precursor powder is preferably 0.01 μm or more and less than 0.7 μm, more preferably 0.03 μm or more and 0.6 μm or less, further preferably 0.05 μm or more and 0.5 μm or less, particularly preferably 0.08 μm or more and 0.4 μm or less, and most preferably 0.1 μm or more and 0.3 μm or less. In this case, it is possible to make it easier for either Na3Fe2(PO4)P2O7 crystal or Na4Fe3(PO4)2P2O7 crystal to precipitate.

[0066] In the present invention, the average particle size is the average particle size (D 50 In the examples of this specification, a laser diffraction particle size distribution measuring device, product number "SALD-2200" manufactured by Shimadzu Corporation, was used to measure the average particle size (D 50 ).

[0067] Solid electrolyte powder:

[0068] The solid electrolyte powder can use the powder of the solid electrolyte described above. The average particle size of the solid electrolyte powder is preferably 0.05 μm or more and 3 μm or less, more preferably 0.05 μm or more and less than 1.8 μm, further preferably 0.05 μm or more and 1.5 μm or less, particularly preferably 0.1 μm or more and 1.2 μm or less, and most preferably 0.1 μm or more and 0.7 μm or less. In this case, it is possible to make it easier for either Na3Fe2(PO4)P2O7 crystals or Na4Fe3(PO4)2P2O7 crystals to precipitate.

[0069] In addition, if the average particle size of the solid electrolyte powder is too small, it is not only difficult to mix evenly with the positive electrode active material precursor powder, but also it is possible to reduce the ionic conductivity of the electrode material layer due to moisture absorption and carbonation, or promote excess reaction with the positive electrode active material precursor powder. As a result, there is a tendency for the internal resistance of the electrode material layer to increase, and the voltage characteristics and charge and discharge capacity to decrease. On the other hand, if the average particle size of the solid electrolyte powder is too large, the softening flow of the positive electrode active material precursor powder is significantly hindered, so there is a tendency for the obtained secondary battery positive electrode to have poor smoothness and reduced mechanical strength, or increased internal resistance.

[0070] Adhesives:

[0071] Binders are materials used to integrate raw materials (raw material powders) with each other. Examples of binders include cellulose derivatives such as carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, ethyl cellulose, hydroxyethyl cellulose, and hydroxymethyl cellulose, or water-soluble polymers such as polyvinyl alcohol; thermosetting resins such as thermosetting polyimide, phenolic resin, epoxy resin, urea resin, melamine resin, unsaturated polyester resin, and polyurethane; polycarbonate resins such as polypropylene carbonate; and polyvinylidene fluoride.

[0072] [Positive electrode for all-solid-state sodium-ion secondary battery and all-solid-state sodium-ion secondary battery]

[0073] Figure 1 Schematic cross-sectional view of an all-solid-state sodium ion secondary battery according to one embodiment of the present invention. Figure 1 As shown, the all-solid-state sodium ion secondary battery 1 includes a solid electrolyte layer 2 , a positive electrode layer 3 , a negative electrode layer 4 , a first current collector layer 5 , and a second current collector layer 6 .

[0074] The solid electrolyte layer 2 has a first main surface 2a and a second main surface 2b facing each other. A positive electrode layer 3 is provided on the first main surface 2a of the solid electrolyte layer 2. The positive electrode layer 3 is a positive electrode for an all-solid-state sodium ion secondary battery. In addition, a first collector layer 5 is provided on the main surface of the positive electrode layer 3 on the opposite side to the solid electrolyte layer 2.

[0075] A negative electrode layer 4 is provided on the second main surface 2b of the solid electrolyte layer 2. A second current collector layer 6 is provided on the main surface of the negative electrode layer 4 opposite to the solid electrolyte layer 2. The first current collector layer 5 and the second current collector layer 6 may not be provided.

[0076] Hereinafter, the details of each layer of the all-solid-state sodium ion secondary battery of the present invention will be described.

[0077] (Positive electrode layer)

[0078] The positive electrode layer is composed of the positive electrode composite material for a secondary battery of the present invention.

[0079] The thickness of the positive electrode layer is preferably 10 μm or more, more preferably 30 μm or more, further preferably 50 μm or more, particularly preferably 70 μm or more, and most preferably 100 μm or more. In this case, the capacity of the secondary battery can be further effectively increased. On the other hand, if the thickness of the positive electrode layer is too thick, the resistance to electron conduction increases, the discharge capacity and the operating voltage decrease, and in addition, the stress caused by the shrinkage during firing increases, resulting in peeling, so the thickness of the positive electrode layer is preferably 1000 μm or less.

[0080] In addition, the amount of positive electrode active material contained in the positive electrode layer is preferably 1 mg / cm 2 More preferably 3 mg / cm 2 More preferably, 5 mg / cm 2 Above, particularly preferably 7 mg / cm 2 Above, most preferably 10 mg / cm 2 In this case, the capacity of the secondary battery can be further effectively increased. The upper limit of the amount of positive electrode active material is not particularly limited, and can be set to 500 mg / cm 2 .

[0081] (Solid electrolyte layer)

[0082] The solid electrolyte layer can be manufactured by mixing raw material powders (solid electrolyte powders), shaping the mixed raw material powders (solid electrolyte powders), and then firing. For example, it can be manufactured by slurrying the raw material powders (solid electrolyte powders) to make green sheets, and then firing the green sheets. In addition, it can also be manufactured by a sol-gel method. As the solid electrolyte powder, the same solid electrolyte powder as the solid electrolyte powder described in the column of the positive electrode for secondary batteries can be used.

[0083] The average particle size of the solid electrolyte powder is preferably 0.01 μm or more and 3 μm or less, more preferably 0.03 μm or more and less than 1.8 μm, further preferably 0.03 μm or more and 1.5 μm or less, particularly preferably 0.03 μm or more and 1.2 μm or less, and most preferably 0.03 μm or more and 0.7 μm or less. If the average particle size of the solid electrolyte powder is too small, it is possible that the ion conductivity of the solid electrolyte layer is reduced due to moisture absorption and carbonation. As a result, there is a tendency for the voltage characteristics and charge and discharge capacity of the secondary battery to decrease. On the other hand, when the average particle size of the solid electrolyte powder is too large, there is a tendency for the internal resistance of the secondary battery to increase.

[0084] The thickness of the solid electrolyte layer is preferably 5 μm to 1000 μm, more preferably 10 μm to 200 μm. If the thickness of the solid electrolyte layer is too thin, the mechanical strength is reduced and it is easy to break, so it is easy to cause an internal short circuit. When the thickness of the solid electrolyte layer is too thick, the sodium ion conduction distance accompanying charge and discharge becomes longer, so the internal resistance becomes higher, and the discharge capacity and operating voltage of the secondary battery are easily reduced. In addition, the energy density per unit volume of the secondary battery is also easily reduced.

[0085] (Negative electrode layer)

[0086] The negative electrode active material contained in the negative electrode layer is not particularly limited, and for example, carbon electrode materials such as hard carbon and soft carbon can be used. The carbon electrode material is preferably hard carbon. However, the negative electrode active material may also include alloy-based negative electrode active materials such as tin, bismuth, lead, phosphorus, etc. that can absorb sodium, or metallic sodium.

[0087] The negative electrode layer may further include a solid electrolyte and a conductive aid. The ratio of each material in the negative electrode layer may be, for example, 60% to 100% of the negative electrode active material, 0% to 35% of the solid electrolyte, and 0% to 5% of the conductive aid in terms of mass %. The solid electrolyte and the conductive aid may be, for example, the substances described in the column of the positive electrode for secondary batteries.

[0088] The thickness of the negative electrode layer is preferably 0.3 μm to 500 μm, more preferably 3 μm to 300 μm. If the thickness of the negative electrode layer is too thin, the absolute capacity (mAh / g) of the negative electrode tends to decrease. When the thickness of the negative electrode layer is too thick, the resistance increases, so the capacity (mAh / g) tends to decrease.

[0089] The negative electrode layer can be made, for example, using a slurry containing a negative electrode active material precursor powder (the slurry contains solid electrolyte powder and a conductive aid as needed). In the slurry, a binder, a plasticizer, a solvent, etc. are added as needed. After the slurry is applied to the main surface of one side of the solid electrolyte layer, it is dried and fired, thereby making the negative electrode layer. In addition, it can also be made by applying the slurry to a substrate such as PET (polyethylene terephthalate) and drying it to make a raw sheet, and firing the raw sheet. Alternatively, the negative electrode layer can also be made of metal, in which case the negative electrode layer can be made by sputtering, evaporation, etc.

[0090] (First current collector layer and second current collector layer)

[0091] The materials of the first collector layer and the second collector layer are not particularly limited, and metal materials such as aluminum, titanium, silver, copper, stainless steel or their alloys can be used respectively. The above metal materials can be used alone or in combination. In addition, these alloys refer to alloys containing at least one of the above metals. The thickness of the first collector layer and the second collector layer is not particularly limited, and can be 0.01 μm or more and 1000 μm or less, respectively.

[0092] The formation method of the first collector layer and the second collector layer is not particularly limited, and for example, physical vapor methods such as evaporation and sputtering, and chemical vapor methods such as thermal CVD, MOCVD, and plasma CVD can be cited. As other formation methods of the first collector layer and the second collector layer, plating, sol-gel method, and liquid phase film forming method based on spin coating can be cited. However, when the first collector layer and the second collector layer are formed on the positive electrode layer and the negative electrode layer respectively by sputtering, the adhesion is excellent, so it is preferred.

[0093] Hereinafter, the present invention will be described in more detail based on specific examples. The present invention is not limited to the following examples at all, and can be implemented with appropriate changes within the scope of the present invention.

[0094] (Example 1)

[0095] (a) Preparation of positive electrode active material precursor powder

[0096] Sodium metaphosphate (NaPO3), iron oxide (Fe2O3) and orthophosphoric acid (H3PO4) are used as raw materials. The raw material powders are prepared in a manner to obtain a composition of 40% Na2O, 20% Fe2O3 and 40% P2O5 in mol%, and melted at 1250°C in an air atmosphere for 45 minutes. Then, the melt is made to flow out between a pair of rotating rollers and is formed while being rapidly cooled to obtain a film-like glass with a thickness of 0.1 mm to 2 mm. The obtained film-like glass is crushed using a ball mill and a planetary ball mill to obtain an average particle size (D50 ) was 0.2 μm glass powder (positive electrode active material precursor powder). In addition, as a result of powder X-ray diffraction (XRD) measurement, it was confirmed that the obtained glass powder was amorphous.

[0097] (b) Preparation of solid electrolyte layer and solid electrolyte powder

[0098] Li2O-stabilized β"-alumina (manufactured by Ionotec, composition formula: Na 1.7 Li 0.3 Al 10.7 O 17 ) was processed into a sheet with a thickness of 0.5 mm, thereby obtaining a solid electrolyte layer. In addition, the average particle size (D 50 ) is a solid electrolyte powder of 2.0 μm.

[0099] (c) Preparation of positive electrode paste

[0100] The positive electrode active material precursor powder obtained was weighed in a manner such that 72% by mass, 25% by mass of solid electrolyte powder, and 3% by mass of acetylene black (TIMCAL, SUPERC65) as conductive carbon (conductive aid) were weighed separately, and a mortar and pestle made of agate were used to mix for 30 minutes to prepare a positive electrode composite material powder. 20 parts by mass of polypropylene carbonate (PPC) was added to 100 parts by mass of the prepared positive electrode composite material powder, and 30 parts by mass of N-methylpyrrolidone were further added. They were fully stirred using a rotation and revolution mixer, and slurried to prepare a positive electrode paste.

[0101] (d) Formation of positive electrode layer

[0102] On one main surface of the solid electrolyte layer, an area of ​​1 cm 2 The positive electrode paste was applied with a thickness of 80 μm and dried at 70°C for 3 hours to form a positive electrode material layer. The formed positive electrode material layer was fired at 550°C for 30 minutes in a mixed gas atmosphere of H24 volume % and N296 volume % to form a positive electrode composite material (positive electrode layer) for secondary batteries on the main surface of one side of the solid electrolyte layer.

[0103] (e) Current collector formation and button cell assembly

[0104] A 100 nm thick aluminum vapor-deposited film was formed on the entire surface of the positive electrode layer as a current collector. Then, in an argon glove box with a dew point below -60°C, metallic sodium, which became the negative electrode layer, was crimped onto the main surface of the solid electrolyte layer on the opposite side of the positive electrode layer and sealed in a CR2032 button cell to produce an all-solid-state sodium ion secondary battery.

[0105] (Examples 2, 3 and Comparative Examples 1, 2)

[0106] An all-solid-state sodium ion secondary battery was prepared in the same manner as in Example 1 except that the secondary battery positive electrode composite material composition and the firing conditions were set as shown in Table 1 below.

[0107] (Example 4)

[0108] As solid electrolyte powder, sodium superion conductor (crystal composition: Na3Zr2Si2PO 12 ) instead of Li2O-stabilized β"-alumina, and except for this, a positive electrode composite material (positive electrode layer) for a secondary battery was prepared in the same manner as in Example 2. In other respects, an all-solid-state sodium ion secondary battery was prepared in the same manner as in Example 2. Therefore, the solid electrolyte layer used Li2O-stabilized β"-alumina in the same manner as in Example 2.

[0109] [evaluate]

[0110] (Powder X-ray diffraction measurement)

[0111] The powder X-ray diffraction measurement of the secondary battery positive electrode composite materials prepared in Examples 1 to 4 and Comparative Examples 1 and 2 was performed. CuKα rays (wavelength ) In addition, as an X-ray diffraction apparatus, a product number "SmartLab" manufactured by Rigaku Corporation was used.

[0112] Figure 2 : is a graph showing the X-ray diffraction spectra of the positive electrode composite materials for all-solid-state sodium ion secondary batteries prepared in Examples 1 to 3 and Comparative Examples 1 and 2. Figure 3 It is a magnified representation Figure 2 The X-ray diffraction spectrum of 2θ = 30° to 40°. Figure 2 and Figure 3 The unit of diffraction intensity is cps.

[0113] Depend on Figure 2 and Figure 3It can be seen that in the positive electrode composite materials for secondary batteries of Examples 1 to 3, a peak was observed at 2θ=33.0°~34.0°, and Na3Fe2(PO4)P2O7 crystals were precipitated. It is believed that by mixing the positive electrode active material precursor and the solid electrolyte in appropriate amounts, the positive electrode active material precursor is fully softened and flowed during firing, and the interface between the positive electrode active material precursor and the solid electrolyte is formed in an appropriate amount, so crystallization from the positive electrode active material precursor to Na3Fe2(PO4)P2O7 is induced. On the other hand, in Comparative Examples 1 and 2, no peak was observed at 2θ=33.0°~34.0°, and Na3Fe2(PO4)P2O7 crystals were not precipitated. It is believed that the reason is that in Comparative Example 1, since a large amount of particulate solid electrolyte was added, the amount of the interface between the positive electrode active material precursor and the solid electrolyte became excessive, inducing crystallization from the positive electrode active material precursor to maricite-type NaFePO4. On the other hand, in Comparative Example 2, the particle size of the positive electrode active material precursor and the solid electrolyte used is large, so the positive electrode active material precursor is difficult to soften and flow during firing. In addition, the surface area of ​​the positive electrode active material precursor and the solid electrolyte is also small, so the amount of interface between the positive electrode active material precursor and the solid electrolyte is also reduced. As a result, it is believed that only crystallization of Na2FeP2O7 occurred from the positive electrode active material precursor.

[0114] In addition, in the secondary battery positive electrode composite material of Example 4 using a sodium superion conductor as a solid electrolyte powder constituting the secondary battery positive electrode composite material, a peak was also observed at 2θ=33.0°~34.0°, confirming the precipitation of Na3Fe2(PO4)P2O7 crystals.

[0115] (Thermal Expansion Coefficient Measurement)

[0116] The thermal expansion coefficients of the secondary battery positive electrode composite materials prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were measured. The thermal expansion coefficients were measured by measuring the average thermal expansion coefficient in the temperature range of 30°C to 300°C using a push rod thermal expansion coefficient measuring device (manufactured by NETZSCH, Dilatometer).

[0117] (Evaluation of battery characteristics)

[0118] For the secondary batteries prepared in Examples 1 to 4 and Comparative Examples 1 and 2, charge and discharge were performed at 60°C, 0.2C and 60°C, 1C, and the initial discharge capacity (hereinafter referred to as discharge capacity) was obtained. The results are shown in Table 1 below. Table 1 also shows the peak position of the X-ray diffraction spectrum in the range of 2θ = 30° to 40° (XRD peak position).

[0119] [Table 1]

[0120]

[0121] As can be seen from Table 1, in Examples 1 to 4 using a secondary battery positive electrode composite material, it can be confirmed that the capacity of the secondary battery can be effectively increased, wherein the secondary battery positive electrode composite material contains a crystal showing a main peak at 33° to 34° when performing powder X-ray diffraction measurement. On the other hand, in Comparative Examples 1 to 2 using another secondary battery positive electrode composite material, the capacity of the secondary battery is insufficient, wherein the other secondary battery positive electrode composite material does not contain a crystal showing a main peak at 33° to 34° when performing powder X-ray diffraction measurement.

[0122] Description of Reference Numerals

[0123] 1…All-solid-state sodium-ion secondary battery

[0124] 2…Solid electrolyte layer

[0125] 2a, 2b…1st and 2nd main surfaces

[0126] 3… Positive electrode layer

[0127] 4…Negative electrode layer

[0128] 5, 6...the first and second current collector layers.

Claims

1. A positive electrode composite material for an all-solid-state sodium ion secondary battery, characterized in that: Include: positive electrode active material; and A solid electrolyte containing at least one selected from β"-alumina, β-alumina and a sodium superion conductor crystal, The positive electrode composite material for an all-solid-state sodium ion secondary battery contains crystals showing a main peak at 33° to 34° when subjected to powder X-ray diffraction measurement.

2. The positive electrode composite material for an all-solid-state sodium ion secondary battery according to claim 1, characterized in that: The crystal showing a main peak at 33° to 34° when performing the powder X-ray diffraction measurement is at least one of Na3Fe2(PO4)P2O7 crystal and Na4Fe3(PO4)2P2O7 crystal.

3. The positive electrode composite material for an all-solid-state sodium ion secondary battery according to claim 1 or 2, characterized in that: The solid electrolyte is at least one of β"-alumina and β-alumina.

4. The positive electrode composite material for an all-solid-state sodium ion secondary battery according to claim 1 or 2, characterized in that: In terms of mass %, the positive electrode active material comprises 30% to 95%, the solid electrolyte comprises 5% to 70% and the conductive additive comprises 0% to 20%.

5. A positive electrode for an all-solid-state sodium ion secondary battery, characterized in that: A positive electrode composite material for an all-solid-state sodium ion secondary battery comprising the material described in claim 1 or 2.

6. An all-solid-state sodium ion secondary battery, characterized in that: It includes the positive electrode for an all-solid-state sodium ion secondary battery as described in claim 5.

Citation Information

Patent Citations

  • Member for power storage device, all-solid battery, and method of manufacturing member for power storage device

    JP2021097034A